STUDI EKSPERIMEN PANEL SURYA DENGAN KOLEKTOR PEMANAS UDARA - Mega Lazuardi Umar; Prabuditya Bhisma Wisnu Wardana; Asmar Finali; Agung Fauzi Hanafi; Rizqi Ilmal Yaqin (P3M Politeknik Negeri Indramayu, 2021)
Solar panel is popular renewable energy technology because it is environmentally friendly, zero emissions, and environmentally clean. However, the energy conversion value from solar radiation to electricity is quiet small, more than 70% of solar radiation is discharged into heat energy. Therefore, a heat collector is needed to take advantage of the heat dissipation from solar panel. In this study, an air heat collector is placed at the bottom of the panel to indicating the potential energy, electrical efficiency and heat efficiency. It was found that solar panels with air heat collectors were able to increase the electrical efficiency of solar panels by 0.70%. The daily primary total energy efficiency value of solar panels with a heat collector is 17.47% higher than a solar panel without a collector. In the future, the results of this research can be a reference for academics and industry to develop their renewable energy potential.